Pressure-Induced Phase Transitions in GeTe-Rich Ge-Sb-Te Alloys across the Rhombohedral-to-Cubic Transitions - Krbal, Miloš; Barták, Jaroslav; Kolář, Jakub; Prytuliak, Anastasiia; Kolobov, Alexander V.; Fons, Paul; Bezacier, Lucile; Hanfland, Michael; Tominaga, Junji (American Chemical Society, 2017)
We demonstrate that pressure-induced amorphization in Ge-Sb-Te alloys across the ferroelectric-paraelectric transition can be represented as a mixture of coherently distorted rhombohedral Ge8Sb2Te11 and randomly distorted cubic Ge4Sb2Te7 and high-temperature Ge8Sb2Te11 phases. While coherent distortion in Ge8Sb2Te11 does not prevent the crystalline state from collapsing into its amorphous counterpart in a similar manner to pure GeTe, the pressure-amorphized Ge8Sb2Te11 phase begins to revert to the crystalline cubic phase at similar to 9 GPa in contrast to Ge4Sb2Te7, which remains amorphous under ambient conditions when gradually decompressed from 40 GPa. Moreover, experimentally, it was observed that pressure-induced amorphization in Ge8Sb2Te11 is a temperature-dependent process. Ge8Sb2Te11 transforms into the amorphous phase at similar to 27.5 and 25.2 GPa at room temperature and 408 K, respectively, and completely amorphizes at 32 GPa at 408 K, while some crystalline texture could be seen until 38 GPa (the last measurement point) at room temperature. To understand the origins of the temperature dependence of the pressure-induced amorphization process, density functional theory calculations were performed for compositions along the (GeTe)(x) - (Sb2Te3)(1-x) tie line under large hydrostatic pressures. The calculated results agreed well with the experimental data.
Tlakové indukované fázové přechody v GeTe-bohatých slitinách Ge-Sb-Te přes přechody rhombohedricko-to-kubické přechody
Keywords: change memory; germanium telluride; thin-films; ge2sb2te5; amorphization; Paměti na bázi fázové přeměny; tellurid germánia; tenké vrstvy; Ge2Sb2Te5; amorfizace